The study of effect of Piperine by hot-plate and Formalin test in mice - AA.Moghaddamnia (Ph.D) (مجله دانشگاه علوم پزشکی گرگان, 2004)
Background & Objective: Black pepper is frequently used in Iranian traditional medicine as an analgesic (E.g, for toothache). This investigation was conducted to evaluate the response of mice to pain induced by hot-plate and Formalin test either with or without Piperine (One of the active substances of the pepper). Materials & Methods: This randomized experimental study was performed on mice. Hot-plate and Formalin tests were planned to pain measurement. The mice were divided into 2 groups in each arm of study (Hot-plate and Formalin test group). The data of control (Saline) and drug (Piperine) groups were separately compared in each arm of study with student t-test and ANOVA. The difference between each point of data was considered significant at P-value under 0.05. Results: There was not a significant difference in tolerance time of subjects between hot-plate and saline groups. Piperine (25, 50 and 75 mg/kg) along with Morphine (10 mg/kg) causes significant increase to saline group in tolerance time and also significant increase to Morphine group, but in Formalin test Piperine could have significant effect in decreasing the pain induced by of Formalin on mice. These effects are comparable with Morphine. In Formalin test, pain has 2 phases. The first phase is acute and the 2nd one is chronic that begins from 15-20 minutes. Acute pain has central effect and chronic pain has peripheral pathway and Piperine causes decreasing response to Formalin test at the first phase of pain. Naloxone can prevent these effects in all groups. In Formalin test and hot-plate, the effect of Piperine were dose dependent. Conclusion: Piperine can centrally act on the nociception pathway and its effect on Opioid system exhibits as an enhancement Opioid effect. The effects are dose dependent and will be inhibited by Opioid antagonist.